Endoscopic ultrasound-guided biliary drainage in malignant hilar obstruction - Se Woo Park (Society of Gastrointestinal Intervention, 2022)
Endoscopic retrograde cholangiopancreatography (ERCP) has been established as a standard modality for the palliation of malignant hilar biliary obstruction (MHBO). However, endoscopic stent placement is not possible in some patients because of failed biliary cannulation or tumor invasion that limits transpapillary approaches. In this situation, percutaneous transhepatic biliary drainage (PTBD) can be a reasonable alternative for failed ERCP. However, PTBD has a relatively high rate of adverse events and is frequently associated with patient inconvenience related to the external drainage catheter. Endoscopic ultrasound (EUS)-guided biliary drainage (BD) has therefore been introduced as a reliable alternative modality to PTBD in cases of failed ERCP due to an inaccessible papilla, gastric outlet obstruction, or surgically altered anatomy for MHBO. Although the field of dedicated stents for EUS-BD is rapidly advancing with increasing innovations, the debate on the most appropriate stent for EUS-guided drainage has resurfaced. Furthermore, some important questions remain unaddressed, such as which stent best improves clinical outcomes and safety in EUS-BD for MHBO. This review summarizes the fundamental principles of BD in MHBO, basic technique, technical challenges, clinical outcomes, safety profiles, comparison with other modalities, and the future perspectives of EUS-BD, especially EUS-guided hepaticogastrostomy or hepaticoduodenostomy, for MHBO.